The decision-making empirical model in vocational high school - Masduki Zakarijah; S. Soenarto; Eko Marpanaji (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
The objectives of this research is to know the pattern of causal relationships inter-variables on the decision-making empirical model in Vocational High School (SMK). The decision-making empirical model in Vocational High School, consisting of variables: (a) the adequacy of Information and Communication Technology (ICT), (b) the benefits of using information systems, (c) the ethics in decision making, (d) the contribution of school and social environments, (e) the intentions of behaviour, and (f) the patterns of decision-making. Relation between variables was tested statistically using path analysis. The results of the research are as follows. The varian explained by each variable is mathematically formulated in: ZY = 0.134 A + 0.141 B + 0.102 C + 0.486 D + 0.193 E. The most dominant effect for direct effect is D to E has ÏDE = 0,47 and the correlation coefficient = 0,709.